Impact of Aerobic Training on Cardiometabolic Markers and Menopausal Symptoms: A Stratified Analysis by Multimorbidity - Juliene G. Costa; Igor M. Mariano; Ana Clara R. Cunha; Juliana C. Silva; Ludimila F. Gonçalves; Mateus L. Rodrigues; Julia B. Tavares; Victor Hugo V. Carrijo; Ana Luiza Amaral; Guilherme M. Puga (International Journal of Environmental Research and Public Health, 2026)
Cardiometabolic multimorbidity is highly prevalent among postmenopausal women and is associated with adverse metabolic outcomes and a greater burden of climacteric symptoms. This secondary analysis of a quasi-experimental controlled clinical trial investigated the effects of a 12-week aerobic training program on climacteric symptoms, menopause-related quality of life, body composition, and cardiometabolic biomarkers in postmenopausal women with and without cardiometabolic multimorbidity. Forty-one postmenopausal women (50–70 years) were allocated to a single-cardiometabolic-condition group (SINGLE, n = 18) or a multimorbidity group (MULTI, n = 23) and completed supervised walking/jogging aerobic exercise three times per week at 65–75% of heart rate reserve. Climacteric symptoms, quality of life, anthropometric measures, body composition, and biochemical markers were assessed before and after the intervention. Generalized Estimating Equations (GEEs) with Bonferroni post hoc adjustment were used to compare group, time and group*time interactions with alpha of 5%. Significant group-by-time interactions were observed for the Menopause Rating Scale total score and psychological symptoms, as well as for the Cervantes Scale total score, indicating greater improvements among women with multimorbidity. The MULTI group demonstrated significant reductions in overall menopausal symptoms, psychological symptoms, and menopause-related quality of life scores following training. Body weight, triglycerides, and very-low-density lipoprotein cholesterol also decreased significantly only in the MULTI group, whereas several body composition parameters improved over time regardless of cardiometabolic burden. These findings indicate that aerobic training may be associated with improvements in menopausal symptoms, quality of life, body composition, and selected cardiometabolic markers in postmenopausal women, with some outcomes showing greater changes among women with cardiometabolic multimorbidity.